Cover Image. Issue 3 (10th June 2021) - Unknown
Abstract : How do blind polymer molecules find the right way to crystal nucleation? It is a struggling journey. Shown in the cover image, polymer molecules try various possible paths to reach the destination. But the fastest and stable path always prevails. The perspective (e10173) by Xu et al. discusses both the thermodynamic and kinetic factors affecting secondary nucleation of flexible polymer chains on the crystal growth front, focusing on the interplay of various processes, such as attaching vs detaching, inter‐chain vs intra‐chain nucleation, thickening and widening, etc. Image credit: Zhiqi Wang. (doi.org/10.1002/pcr2.10173 )